Sustainable irrigation management and farmers' knowledge in South Khorasan, Iran. (16th January 2020) - Bakhshi, Azadeh; Cecchini, Lucio; Ghanian, Mansour; Pour, Bahman Khosravi; Santucci, Fabio Maria
This paper presents the results of a study investigating groundwater management in Iran, where water is private and its allocation still follows traditional rules. It represents a portion of a wider multidisciplinary research, conducted with the sustainable livelihood approach. A survey was carried out in August 2017, with 237 respondents and a questionnaire with 92 questions. For this article only 15 variables were retained, to analyse the human capital and the relationships with the extension service. Three clusters of respondents have been statistically designed. The farmers' formal education is relatively low, age is high and the awareness about the need for better management is low. The public extension service does not appear to be very effective and participation in its activities is low. Further research is needed to assess which actions and media can be used for improving the attitudes, knowledge and practices related to water management.